Payment and settlement systems in Finland 1995 - Veikko Saarinen; Kirsti Tanila; Kimmo Virolainen (Bank of Finland, 1996)
This paper is an overview of domestic payment and settlement systems in Finland.It contains an up-to-date description of institutional aspects of payment systems, payment media used by non-banks, interbank exchange and settlement circuits and securities settlement systems.At the end of the paper, annual statistics are presented on payment and settlement systems and on payment media for the years 1989-1994
URN:NBN:fi:bof-20140807522
Keywords: 330; clearing; settlement; payment media; Finland